Identifying Common Errors in Speaking English among Fourth-Semester Students of IGM University - Teddy Samsidi (Global Expert: Jurnal Bahasa dan Sastra, 2024)
English speaking skills English teachers play an important role in helping students to achieve their goals of learning the language. Appropriate techniques for improving this skill must be considered by students of the English language education program or FKIP, where students are prospective English teachers. This research examines whether it is effective for learning English speaking skills. This research used a test with a sample of 8 participants for the 2024/2025 academic year. The data from the results of this research are analyzed qualitatively. These results show that it is effective in learning English because, from the test results, this technique is therefore an alternative learning technique that English teachers can use in learning to speak English. Education is a fundamental pillar of individual and societal development, which plays a vital role in shaping the future of a nation. In Indonesia, education is highly valued, and efforts have been made to improve the quality and accessibility of education throughout the country. In line with global trends, English has become an important language in education and communication and is recognized as a lingua franca for international interaction. Indo Global Mandiri Palembang, the purpose of identifying common errors is to find errors and correct them when pronouncing and also to become good words in speaking so that students understand when pronouncing or speaking and also to make the correct words and participants in this study were 8 people, the results of common errors correcting words, pronunciation and correct speaking Conclusion This study was conducted to find out common errors that occur when students speak. Some of the errors that can occur in students when speaking include Mispronunciation of Articles and Plural Nouns, Misuse of Prepositions, Misorder of Words, and Confusing Homophones. However, the identification carried out showed that the errors that were often made were related to pronunciation errors and word order errors. Keywords: Speaking, Proficiency, Common Error